2014
DOI: 10.1002/ajmg.b.32254
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic scores associated with educational attainment in adults predict educational achievement and ADHD symptoms in children

Abstract: The American Psychiatric Association estimates that 3 to 7 per cent of all school aged children are diagnosed with attention deficit hyperactivity disorder (ADHD). Even after correcting for general cognitive ability, numerous studies report a negative association between ADHD and educational achievement. With polygenic scores we examined whether genetic variants that have a positive influence on educational attainment have a protective effect against ADHD. The effect sizes from a large GWA metaanalysis of educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 43 publications
10
42
0
1
Order By: Relevance
“…The genetic effect in our US sample of EA respondents was small in magnitude, (r=0.18, see Table 2) consistent with published estimates from samples in the UK and the Netherlands (Ward et al 2014, De Zeeuw et al 2014). In years of educational attainment, this correlation is equivalent to a predicted increase of 0.41 years for a one SD increase in the polygenic score.…”
Section: Resultssupporting
confidence: 89%
“…The genetic effect in our US sample of EA respondents was small in magnitude, (r=0.18, see Table 2) consistent with published estimates from samples in the UK and the Netherlands (Ward et al 2014, De Zeeuw et al 2014). In years of educational attainment, this correlation is equivalent to a predicted increase of 0.41 years for a one SD increase in the polygenic score.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with previous findings that have documented a link between polygenic propensity for educational attainment and post‐secondary education with an attenuation in the variance observed in African American samples, a greater polygenic propensity for educational attainment was associated with attending a higher education institution and accounted for 1.30% of the variance in this outcome. Higher polygenic propensity for educational attainment has been extensively linked to higher cognitive faculties and executive functioning .…”
Section: Discussionsupporting
confidence: 90%
“…For example, PRSs were able to explain 6% of the variation in schizophrenia diagnostic rates, a considerable improvement compared to the variation explained by individual variants, which was less than 1% (Ripke et al, 2011). Other psychiatric phenotypes (e.g., de Moor et al, 2015; de Zeeuw et al, 2014; Hamshere et al, 2013a; 2013b; ISC, 2009; Ruderfer et al, 2013; Sklar et al, 2011) have demonstrated similar results using cumulative measures of genetic risk, including tobacco and other substance use phenotypes (Salvatore et al, 2014). PRSs for variants associated with CPD in the Tobacco and Genetics Consortium (TAG) meta-analysis (Tobacco and Genetics Consortium [TAG], 2010) significantly predicted tobacco use at ages 20 and 24 (Vrieze et al, 2012), and in another study, explained a small but significant proportion of the variation in number of drinks consumed per week (0.4–0.5%) and age of cannabis initiation (0.6–0.9%; Vink et al, 2014).…”
Section: Introductionmentioning
confidence: 81%